Effects of Stunting on Child Development: A Meta-Analysis - Rosyidah, Milatur; Dewi, Yulia Lanti Retno; Qadrijati, Isna (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Stunting is a condition where children under five have a low height for their age. Stunted children under five have a nutri